2022
DOI: 10.53708/hpej.v5i1.1265
|View full text |Cite
|
Sign up to set email alerts
|

Examination Anxiety in Integrated Modular Curriculum: Perceptions of Dental Students

Abstract: Introduction:The universal driving force for learning is assessment, however, it accompanies anxiety, commonly known as exam or test anxiety. There is increasing evidence that exam modality and gender play a significant role in generating anxiety in medical students. This study was conducted to determine the prevalence of exam anxiety in different assessment modalities with same examination standards and criteria among dental students at University College of Dentistry (UCD), The University of Lahore (UO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another study found that students who were more exam-oriented had lower levels of emotional intelligence and empathy (Liu et al, 2020). Janjua, Khan and Mukhtar (2022) reported that exam-oriented education had a negative impact on affective competence of medical students in Pakistan. A recent study by Barzegar and Fereidooni (2021) examined the relationship between high-stakes exams and Iranian high school students' academic motivation.…”
Section: Exam-oriented Education System and Affective Competencementioning
confidence: 99%
“…Another study found that students who were more exam-oriented had lower levels of emotional intelligence and empathy (Liu et al, 2020). Janjua, Khan and Mukhtar (2022) reported that exam-oriented education had a negative impact on affective competence of medical students in Pakistan. A recent study by Barzegar and Fereidooni (2021) examined the relationship between high-stakes exams and Iranian high school students' academic motivation.…”
Section: Exam-oriented Education System and Affective Competencementioning
confidence: 99%